THE EFFECT OF S ON THE PARTITIONING OF NI BETWEEN OLIVINE AND SILICATE MELT IN MORB - Li C.; Ripley E.M.; Mathez E.A. (My University, 2003)
The partitioning behavior of Ni between olivine and silicate melt in S-bearing systems has been investigated using mid-ocean ridge basalts (MORBs). The Nernst Ni partition coefficient between olivine and silicate melt (DNi) derived from the MORB samples varies between 4 and 9, values that are up to 50% lower than those derived from S-free experimental systems of similar composition. The MORB samples yield lower DNi values because Ni2+ and S2- interact to form a Ni-S complex in the silicate melt. Since the Ni present as NiS contributes to the melt concentration but is not available for sequestration by olivine, the overall effect is a reduction in the DNi value calculated from the total concentration of Ni in the silicate melt. This hypothesis is supported by the negative correlation between the lnKDNi-Mg (KDNi-Mg=[MgOmelt/MgOOl]/[NiOmelt/NiOOl]) values and the contents of S in the silicate melts of the MORB samples.
Keywords: NICKEL; SULFUR; OLIVINE; BASALT; PARTITION COEFFICIENT